Efeitos do treinamento concorrente sobre aspectos bioquímicos, antropométricos, funcionais e hemodinâmicos de mulheres diabéticas do tipo 2 - Paulino, Heverton; Aguiar, Renata Emília Marques; Teixeira, Cauê La Scala; Dos Santos, Gilberto Monteiro; Ferreira, Sionaldo Eduardo; Pauli, José Rodrigo; Colantonio, Emilson; Medeiros, Alessandra; Gomes, Ricardo José [UNESP] (My University, 2015)
Aim: The aim of this study was to investigate the effects of concurrent training on biochemical, anthropometric, hemodynamic and functional parameters in diabetic women. Methods: The sample was composed of 16 type 2 diabetic women aged 62.8 ± 9,5 years. Physical exercises were performed three times per week, lasting 60 minutes per session. The training sessions were composed of aerobic followed by resistance exercises. Data collection was based on functional parameters (functional fitness tests), biochemical (plasma glucose, cholesterol and triglycerides), anthropometric (height, body mass, body mass index and waist circumference) and hemodynamic (blood pressure). Results: The data showed a significant improvement in strength endurance, coordination, general physical fitness index, fasting blood glucose and systolic and diastolic pressure resting. Other parameters showed no significant difference. Conclusion: The concurrent training was effective in promoting significant changes in parameters related to the health of women with diabetes type 2.
Effects of concurrent training on biochemical, anthropometric, hemodynamic and functional parameters of type 2 diabetic women
Keywords: Blood glucose; Blood pressure; Concurrent training; Diabetes mellitus; Physical exercise